ответ:3*9^(x-1/2)-7*6^x + 3*4^(x+1)=0
3*9^x*9^(-1/2)-7*6^x+3*4^x*4=0
9^(-1/2)=1/3, 3*(1/3)=1, 3*4=12
9^x-7*6^x+12*4^x=0,
т.к. 4^x≠0 поделим обе части уравнения на это выражение
(9/4)^x-7*(3/2)^x+12=0
пусть (3/2)^x=y, тогда уравнение примет вид
у^2-7y+12=0, y=3, y=4
(3/2)^x=3 или (3/2)^x=4
x=log(1.5)3 x=log(1.5)4 (1,5 - основание логарифма)
ответ: log(1.5)3 , log(1.5)4
log(1.5)3= log(1.5)(2*1,5)= log(1.5)(1,5)+ log(1.5)2=1+log(1.5)2
1<log(1.5)2<2, 2<1+log(1.5)2<3
log(1.5)3 ∈[2,3]
log(1.5)3<log(1.5)4 < log(1.5)(4 .5)
2<log(1.5)4 < log(1.5)(4 .5)
log(1.5)(4 .5)=log(1.5)(3*1.5)=log(1.5)(1.5)+log(1.5)(3)=1+1+log(1.5)2>3
log(1.5)4 ∉[2,3]
ответ:
пошаговое объяснение:
1) x+23=41 4) x-61=17
x=18 x=78
2) 36+y=74 5) 46-y=24
y=38 y=22
3) 85+z=97 6) 53-z=25
z=12 z=28
= 10-(7/3*9/2-5/2*5/2)*1/4=10-(7*3/2-25/4)*1/4=10-(21/2-25/4)*1/4=10-17/4*1/4=10-17/16=8 целых 15/16